(untitled) (American Journal of Pediatric Medicine and Health Sciences (2993-2149), 2025)
This article compares changes in the acute phase of myocardial infarction, comparative studies were conducted on changes in renal glomeruli and tubules using troponin, creatinine, cystatin C, neutrophil gelatinase-associated lipocalin (NGAL), and kidney injury molecule-1 (KIM-1). The obtained results indicate that NGAL, compared to cystatin C and KIM-1, allows for earlier detection of acute kidney injury that develops during the acute phase of myocardial infarction.